Gene Expression and Control 2019
DOI: 10.5772/intechopen.81253
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Approaches for Understanding of Regulation of Expression of the Urea Cycle Genes

Abstract: Urea cycle converts ammonia, a waste product of protein catabolism and a neurotoxin, into non-toxic urea. Urea cycle disorders are a group of rare genetic diseases that have protein-restricted diet as a common treatment modality. Expression of urea cycle genes is regulated in concert by the dietary protein intake, but the mechanism of this regulation is not well understood. Data mining of databases such as ENCODE and Cistrome can be used to gain new information about regulatory elements, transcription factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 84 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Downloaded sequences were aligned using Clustal Omega (Sievers et al, 2011) and the alignment was visualized with WebLogo 3 (Crooks et al, 2004). Histone modifications of the −3 kb enhancer and transcription factors that bind to it were identified by data mining the ENCODE project database (Ljubica Caldovic [July 20, 2020]) (Caldovic, 2018). The following filters were applied to the experiment matrix in the ENCODE database: TF ChIP‐seq, Histone ChIP‐seq, organism ( H. sapiens ), and biosample term name (liver); results were visualized in the UCSC Genome Browser for the chr17: 42,078,635–42,079,129 genomic region.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Downloaded sequences were aligned using Clustal Omega (Sievers et al, 2011) and the alignment was visualized with WebLogo 3 (Crooks et al, 2004). Histone modifications of the −3 kb enhancer and transcription factors that bind to it were identified by data mining the ENCODE project database (Ljubica Caldovic [July 20, 2020]) (Caldovic, 2018). The following filters were applied to the experiment matrix in the ENCODE database: TF ChIP‐seq, Histone ChIP‐seq, organism ( H. sapiens ), and biosample term name (liver); results were visualized in the UCSC Genome Browser for the chr17: 42,078,635–42,079,129 genomic region.…”
Section: Methodsmentioning
confidence: 99%
“…Because phastCons scores of the two intronic sequence variants indicated that they reside in a region of high sequence conservation, we used data mining approaches to further characterize this region (Caldovic, 2018). Query of the phastCons conservation track of the UCSC Genome Browser revealed a 200 bp conserved element with genomic coordinates chr17: 42,082,680-42,082,799 (GRCh37/hg19 human genome assembly) in the first intron of the NAGS gene, which is 547 bp long (Figure 1a).…”
Section: Plasmid Construction and Expression Studiesmentioning
confidence: 99%
See 1 more Smart Citation